DIMENSI SPIRITUALITAS MUSIK SEBAGAI MEDIA EKSISTENSI DALAM SUFISME JALALUDDIN RUMI - Abdulloh Hanif; Ahmad Fathy (FiTUA: JURNAL STUDI ISLAM, 2023)
Music in Islam is not only related to art and culture. It is also included in the discourse of religious worship and experience. Many jurists debate the legal status of music, both at the listening level and at the singing level. However, for Sufis, music is a medium of worship, a medium for expressing their experience of closeness to God. Jalaluddin Rumi, as a Sufi who often uses music and expresses his Sufi experiences through poetry and music. He has a different meaning about music, which seems to contain a spiritual (ruhani) element which is a form of his experiential existence. This issue will be explored in this article through the question: what spiritual values are contained in Sufi music? and how can music occur as a way of existence in Sufism? This research is qualitative in nature with descriptive analysis which results in the conclusion that Rumi's poetry and music show his more intimate and secret teachings in relation to the expression of his relationship with God. So the experience of ecstasy and the ma’rifat often arises through poetry or music.